THE EFFECT OF EXPERIENCE VALUE CUSTOMER TO LOYALTY PRODUCT GARNIER BRAND COSMETICS IN THE COMMUNITY OF LHOKSEUMAWE CITY - Yuliana Wardana; T. Edyansyah; Mohd. Heikal; Heriyana (RADJA PUBLIKA, 2024)
This research examines the influence of functional value, emotional value and social value on loyalty to Garnier Brand cosmetic products in the people of Lhokseumawe City. This research obtained data by distributing questionnaires as a data collection instrument. This research uses a quantitative approach with multiple linear regression analysis with the help of the SPSS (Statistical Package for the Social Sciences) tool. The sampling technique used is a non-probability sampling technique with a sampling technique using purposive sampling as the determinant of the sample. The population is 120 respondents who use Garnier brand cosmetics in Lhokseumawe City. Partial test results show that Functional Value has a positive and significant effect on brand loyalty, Emotional Value has a positive and significant effect on brand loyalty, and Social Value has a positive and significant effect on brand loyalty.